Evidence for intercontinental parasite exchange through molecular detection and characterization of haematozoa in northern pintails (Anas acuta) sampled throughout the North Pacific Basin. Issue 1 (April 2015) - Ramey, Andrew M.; Schmutz, Joel A.; Reed, John A.; Fujita, Go; Scotton, Bradley D.; Casler, Bruce; Fleskes, Joseph P.; Konishi, Kan; Uchida, Kiyoshi; Yabsley, Michael J.
Graphical Abstract